2022
DOI: 10.1155/2022/7598427
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Characteristics of Common Tongue Coatings in Patients with Precancerous Lesions of the Upper Gastrointestinal Tract

Abstract: The tongue coating (TC) microbiota, a crucial component of the tongue coating, illustrates a huge microbial percentage of the body that mostly includes actinobacteria, bacteroides, firmicutes, and fusobacteria. The TC microbiota is closely related to the development of upper gastrointestinal malignancies, such as oral, gastric, and esophageal cancer. Nonetheless, the microbiological characteristics of common TCs in individuals with precancerous lesions of the upper gastrointestinal tract are still unclear. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“… 32 Therefore, we simultaneously investigated the diagnostic value of tongue images and the tongue coating microbiome in GC. Previous studies have shown that the tongue coating microbiome can be used as a diagnostic tool for malignant tumours, including EC, 33 GC 34 and LC. 35 Our study once again confirmed the diagnostic value of the tongue coating microbiome in GC.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Therefore, we simultaneously investigated the diagnostic value of tongue images and the tongue coating microbiome in GC. Previous studies have shown that the tongue coating microbiome can be used as a diagnostic tool for malignant tumours, including EC, 33 GC 34 and LC. 35 Our study once again confirmed the diagnostic value of the tongue coating microbiome in GC.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Actinomyces, Atopobium, Lachnoanaerobaculum, Stomatobaculum and Veillonella of Hp positive patients with dampness-heat syndrome of spleen and stomach was significantly increased (P <0.05).The relative abundances of Mycoplasma, Clostridium_sensu_stricto_1 and Escherichia-Shigella were significantly decreased (P <0.05).The variation of salivary microbiota at genus level is illustrated.Wang J and Kong C [35][36] showed that Clostridium_sensu_stricto_1 and Escherichia-Shigella belong to probiotics.The beneficial bacteria in the saliva of patients with dampness and heat syndrome of spleen and stomach are reduced and the bacteria are disordered.The relative abundance of Mycoplasma decreased in contrast to BT group. We believe that Mycoplasma may reflect the difference between the two syndrome types.Actinomyces are opportunistic pathogens that mainly inhabit the oral cavity and upper respiratory tract, and overgrowth of this genus can cause inflammation [37] belongs to the unique oral bacteria community [38] .Some studies have shown [39][40][41] that oral microbiota can excavate unique biomarkers in diseases, so this study has its research significance.Actinomyces, Atopobium, Lachnoanaerobaculum, Stomatobaculum and Veillonella may be the unique biomarkers of spleen and stomach damp-heat syndrome of Helicobacter pylori infection-related gastritis.…”
Section: Discussionmentioning
confidence: 88%
“…The genus Leptotrichia has been reported to be more significantly abundant in saliva samples from NPC patients than in healthy controls [ 29 ]. A study speculated that Leptotrichia may promote carcinogenesis by influencing the immune–inflammatory response [ 79 ]. Our results support associations between these taxa and NPC, but the detailed mechanisms in the carcinogenesis process are not clear yet.…”
Section: Discussionmentioning
confidence: 99%